Implementasi metode multiple linear regression untuk prediksi harga rumah - Mufidah, Hanifatul (Maliki Interdisciplinary Journal, 2024)
Home is one of the most important needs of the community, so owning a home is something that cannot be avoided. The house functions as a shelter, a place to rest after the stress of everyday life. It is very important to plan so that each family has its own place to live. This planning requires a projection of future prices. With the times, predictions are used as a tool, and even predictions are used as a factor in making purchasing decisions. From research conducted by Sefto P. (2016) in a study entitled "Predicting Land Prices Using a Linear Regression Algorithm," it seems that linear regression can provide measurement results with a high degree of accuracy. High accuracy and lowest RMSE (root mean square error) with 90% training data points and 10% remaining data for testing.